PERLINDUNGAN HUKUM TERHADAP TUNGGAKAN GAJI PEMAIN SEPAK BOLA PROFESIONAL DALAM KONTRAK KERJA DENGAN KLUB SEPAK BOLA BERDASARKAN ASAS LEX SPORTIVA - Yanutama, Abimanyu (Universitas Negeri Semarang, 2024)
The sport of football in this day and age both on an international and national scale at this time has become a very large industry no longer just entertainment or sports facilities so that it is attractive to some entrepreneurs so that it also causes football to have a very close attachment to money, where there are player salaries that must be paid by clubs that have been listed in an employment contract agreement. However, in Indonesia itself there is often non-payment of professional soccer players' salaries by their clubs. This happens because of the lack of protection and understanding of the law by professional soccer players regarding the rights they have. This study uses a normative juridical approach in the hope that it can provide an understanding of the Lex Sportiva principle for professional soccer players in Indonesia by also paying attention to the regulations in force in Indonesia.